A SELF-DETERMINATION THEORY PERSPECTIVE OF STUDENT PERFORMANCE AT THE END OF A VOLLEYBALL UNIT IN COMPULSORY HIGH SCHOOL PHYSICAL EDUCATION - Jody Langdon; Collin Webster; Tina Hall; Eva Monsma (Sport Scientific And Practical Aspects, 2025)
Physical Education (PE) research has shown that students’ in-class performance on a range of tasks can be explained using self- determination theory (SDT). However, little attention has been given to students’ applied motor skill performance from an SDT perspective. Therefore, the purpose of this study was to examine relationships between students’ perceived autonomy support, basic need satisfaction, autonomous motivation, applied volleyball skills, volleyball knowledge, and attitude towards a PE course. Participants included students (N = 141; M age= 14.90, age range: 14-18 years) and teachers (N = 4; Mage= 41.25, age range: 29-56 years) from four intact PE classes at one large high school in the Southeastern United States. Students completed questionnaires assessing perceived autonomy support, basic need satisfaction, autonomous motivation, and attitude towards the PE course. Skills and knowledge were assessed using standardized performance-based protocols. Structural equation modeling indicated that perceived autonomy support was positively related to basic need satisfaction and attitude towards PE directly. Perceived autonomy support also appeared to facilitate students’ applied volleyball performance and game-relevant knowledge through the mediation model proposed by SDT. Pedagogical implications reflected in the interrelated psychological constructs are offered.